Social immersion, spatial bricolage and entrepreneurship in the context of traditional communities - Fortes, Gustavo Passos; Borges Junior, Cândido Vieira (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
Entrepreneurship can be a way to improve life in traditional communities by seeking to harness the potential of the local culture. Social immersion helps learn the dynamics of entrepreneurship in community contexts by contributing to the understanding of the logic of embeddedness, identifying opportunities for collective actions through spatial bricolage. Thus, in the traditional community context, spatial bricolage shows possibilities for joint actions by the population that are in line with customs and traditions. This essay discusses elements of spatial bricolage in the context of social immersion in entrepreneurship in traditional communities considering embeddedness as an element of spatial bricolage by understanding that local potential can only be seized by members aligned with the local culture.